PENGEMBANGAN SISTEM PENGHANTARAN OBAT BERTARGET MITOKONDRIA DAN APLIKASINYA DALAM PENGHANTARAN ZAT ANTIOKSIDAN - Pratiwi, Cellina
Mitochondria are organelles that have the main function as a source of energy. Energy in the form of Adenosine Triphosphate (ATP) is produced in mitochondria through oxidative phosphorylation process which also produces ROS, therefore mitchondria is one of the source of ROS. Excessive ROS production can lead to oxidative stress and mitochondrial dysfunction, which have been associated with a number of disorders such as neurodegenerative, cardiovascular dan diabetes. Targeted delivery system to mitochondria is expected to effectively deliver antioxidant compounds to mitochondria and prevent cell damage due to oxidative stress. In this study, a liposome-based nanocarrier system was developed by conjugation of mitochondriotropic compound dequalinium (DQA). The lipid components used are 1,2-dioleyl-sn-glycero-3-phosphoethanolamine (DOPE) as the main lipid and cholesterol as an auxiliary lipid. Three formulas of Liposome-DQA (LipoDQ) were made with varying concentrations of DQA namely 1,375 mM (LipoDQ LD), 2,75 mM (LipoDQ MD) and 5,5 mM (LipoDQ HD). Nanoparticles with size <200 nm and polydispersity index <0.5 are obtained for the three variations of the LipoDQ formula. The result of LipoDQ zeta potential measurement is positive which indicates the successful incorporation of cationic dequalinium into the liposome structure. Analysis on the level of accumulation using Confocal Laser Scanning Microscopy (CLSM) on Sertoli cells (TM4) showed high Pearson's Coefficient value for LipoDQ which indicates that most of the nanoparticles can be localized into the mitochondria. From the antioxidant activity test using the DPPH method, the Inhibitory Concentration (IC50) value obtained was not significantly different between LipoDQ and free quercetin. IC50 between (2,95-3,76 µM) also indicates strong antioxidant activities. The antioxidant activity evaluation on TM4 cells showed better activity using mitochondrial-targeted delivery systems (LipoDQ LD) with relatively lower concentrations of quercetin (0,01µM) compared to non-mitochondrial-targeted delivery (Liposomes).